E-237 Ruptured blister-type cerebral aneurysm treated with flow diversion using a novel antiplatelet agent cangrelor. (4th August 2020) - Wilson, T; Ramanathan, D; Dye, J
Abstract : Introduction: Blister type aneurysms are challenging to treat surgically and endovascularly with the ideal treatment approach debated. Recently, endovascular procedures, specifically, flow diversion, gained popularity in treating blister aneurysms; however, the need for dual antiplatelet therapy arouses concern, especially in blister aneurysms with their high risk of intraprocedural rupture that may require further intervention. Cangrelor is a novel intravenous P2Y12 platelet receptor antagonist with reversible binding and rapid onset and offset of action. These characteristics are appealing for use in endovascular procedures and may mitigate some concerns associated with other P2Y12 receptor antagonists. Case Summary: This is a 42-year old female who presented with sudden onset of severe headache, nausea, and vomiting. On exam, she was drowsy with no focal neurologic deficits. Initial CT head, CT angiogram, and digital subtraction angiography (DSA) were negative for aneurysm or other vascular pathology. On post bleed day (PBD) 7, repeat DSA demonstrated severe vasospasm and a nonspecific ectatic segment along the distal intracranial internal carotid artery (ICA). On daily angiograms for intraarterial spasmolysis, the ectatic segment remained unchanged until PBD 14, when it began to enlarge and exhibited rapid growth over several days. Management: We treated this patient endovascularly using a pipeline flow diversion device. Immediately prior to pipeline placement, in addition to aspirin and heparin, we also began infusing cangrelor, a novel, reversible, intravenous P2Y12 platelet receptor antagonist with rapid onset and offset of action. After the procedure, she transitioned from cangrelor to prasugrel. Our patient tolerated the procedure well, and on post-procedure day 4, she was discharged home on daily prasugrel and aspirin. To date, our patient is doing well clinically, and her pipeline appears patent with no evidence of aneurysm recurrence. Conclusion: This is one of the first reports of the use of cangrelor in neuro-endovascular procedures. This is important as cangrelor has the potential for improving the safety of endovascular procedures especially in patients where treatment is associated with high risks of intraprocedural bleeding or other complications that may require further intervention, such as in treatment of blister aneurysms. Disclosures: T. Wilson: None. D. Ramanathan: None. J. Dye: None.